Interaction between konjac glucomannan and tannic acid: Effect of molecular weight, pH and temperature. (September 2019) - He, Yun; Wang, Shishuai; Li, Jing; Liang, Hongshan; Wei, Xianlin; Peng, Dengfeng; Jiang, Zhengqiang; Li, Bin
Abstract: The objective of this study was to investigate the interaction between tannic acid (TA) and konjac glucomannan (KGM) with different molecular weight at different pHs, temperatures and urea concentration. The different molecular weight of KGM without change in primary structure were obtained by ultrasonic treatment. Turbidity titration showed that TA/KGM complexes could form at lower pH. The dynamic light scattering (DLS) and transmission electron microscopy (TEM) results indicated that the TA/KGM complexes assembled into large and uniform colloidal particles and would lead to precipitate with the increase of TA/KGM weight ratio. Isothermal titration calorimetry (ITC) results further revealed two-step binding behavior: the first stage corresponded to soluble complex formation, while the second stage represented aggregation between complexes. When the molecular increased, the transition of TA/KGM mass ratio between stage 1 and stage 2 changed from 3.5 to 3.0. KGM of higher molecular weight needed to bind more TA to move to the next stage. When the pH was 7 at 25 °C, the pH was 3.8 at 40 °C or urea addition, the ITC signal was completely abolished, the formation of complexes between KGM and TA was shown to be highly dependent on pH, temperature, urea concentration, suggesting the main driving force of TA-KGM complexes formation was hydrogen bond. Graphical abstract: Image 1 Highlights: The KGM-TA complexes assembled into large and uniform colloidal particles. The formation showed two-step binding behavior with the increase of mass ratio. Molecular weight of KGM, pH, temperature and urea addition affected the formation of the complexes.